Threadfin bream (Nemipteridae) resources in the sea of Vietnam based on the bottom trawl surveys - Anh, Tran Nhat; Cuong, Tran Van (Vietnam Journal of Marine Science and Technology, 2020)
The threadfin bream (Nemipteridae) resources in the sea of Vietnam were analysed using the results of  bottom trawl surveys conducted by the assessment of living marine resources project in Vietnam (ALMRV) in period 2000–2005 and comprehensive investigation of marine fisheries resources project in Vietnam sea during 2012–2013. Results showed that a total of 23 species belonging to 4 genera of Nemipterus, Parascolopsis, Pentapodus and Scolopsis were recorded. The Southeast region has the highest number of species encountered with 26 species, and the lowest number in Central waters with 16 species. The highest number of species was encountered at 50–100 m depth range with 25 species and the lowest number at the depth of less than 20 m with 9 species. Catch of threadfin bream comprised more than 1% of total catch of surveys. In threadfin bream family, genus Nemipterus was the most abundant, the catch of this genus contributed from 75.1% to 88.4% of the family catch. The catch per unit effort decreased from Northern region to Southern region, while the catch in the Northeast monsoon was higher than in the Southwest monsoon. The biomass of threadfin bream in Vietnamese water was estimated to be 7,534 to 12,229 tons depending on the monsoon patterns